Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T18:16:39+02:00
A)
s=a/bx |*bx
a=sbx |/sb
x=a/sb
b)
t=1/abx |*abx
tabx=1 |/tab
x=1/tab
c)
y=2t-3x |-2t
y-2t=-3x |*(-1)
2t-y=3x |/3
(2t-y)/3=x
d)
y=2(x-1) |/2
y/2=x-1 |+1
x=y/2+1
e)
y=(x-1)/2 |*2
2y=x-1 |+1
2y+1=x
f)
y=2/x-1 |+1
y+1=2/x |*x
(y+1)*x=2 |/(y+1)
x=2/(y+1)
g)
p=1/3(a²+2ax) |*(1/3)
p/3=a²+2ax |-(a²)
p/3 - a²=2ax |/2a
(p/3 - a²)/2a = x
2010-04-14T18:25:02+02:00
A) Sbx=a /:Sb
x=abS
b) Tabx = 1
Tab = x
c) y=3x = 2t
3x = 2t-y
x = (2t-y)/3
d) y/2 = x-1
y/2 +1 = x
e) 2y = x-1
2y + 1 = x (tu potraktowałem, ze (x-1) dzielone jest przez 2, a nie x - (1/2) )
f) y (x-1) = 2
yx - y = 2
x-1 = 2/y
x = (2/y) + 1
g) P = 1/3a[kw] + 2/3ax
3P = a[kw] + 2ax
3P - 2ax = a[kw]
-2ax = a[kw] - 3P
2x = - ( [a[kw] - 3P]/a)
x = - ( [a- 3P/a]/2 )